KUALITAS AUDIT SEBAGAI PEMODERASI PENGARUH MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN - I Putu Edi Darmawan (Universitas Muhammadiyah Malang, 2020)
This study aims to test and analyze the impact of accrual earnings management and real earnings management on firm value empirically. Also, audit quality's role on the effect of accrual earnings management and total earnings management on firm value. The analytical method used is Moderated Regression Analysis (MRA). This research's population is manufacturing companies listed on the Indonesia Stock Exchange during the period 2013 to 2017. The sampling technique used is purposive sampling. This study found that accrual earnings management, which is proxied by discretionary accruals, positively affects firm value. Real earnings management has a negative effect on firm value. Audit quality cannot weaken the effect of accrual earnings management on firm value. However, audit quality weakens the effect of real earnings management on firm value.